(3GdecJaj aj Gdhba hGdGHJOGs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3fGUjI eOjfI efa s)
(3ChdgG (B:s
(3gPG cJGH Gdhba GdJGe GbJVjJg ef CbGhjd GdeaSQjf hef cJH GdbQGA hGdfMhjjf hGLJgOJ ai LeY eJaQbg s
(3BNQgG (B:s
(3bGdJ ef Udi GdLeYI Ke bQC HYOgG bd gh Gddg CMO hGdeYhPJjf MaX Ch cai ef eLdSg Pdc BNQ GdcJGH s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1812s
Keywords: (3GdbQGAGJ hGdJLhjOs